Method for producing a friction material, in particular for producing a brake pad, and related brake pad

By using binders composed almost entirely of geological polymers and suitable components, combined with technology to control moisture content, safety risks and production problems in the preparation of friction materials in the prior art are solved, and efficient and safe Frictional material preparation and good braking performance.

CN119451924APending Publication Date: 2025-02-14ITT ITAL SRL
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380050386.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-06-09
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art has operating safety risks and production problems when preparing friction materials, such as dry grinding of caustic soda produces corrosive powders, and the soda powder absorbs water and causes the friction material layer to peel off and crack.

Method used

Using binders composed almost entirely of geological polymers, combined with inorganic fibers, friction modifiers or lubricants, and inorganic or metal fillers, control the moisture content of the geological polymers from 4% to 16 through specific mixing and forming processes. % to improve the mechanical properties and braking performance of the friction material.

Benefits of technology

The safe and efficient preparation of friction materials is achieved, operating risks and production problems are avoided, good braking performance and friction characteristics are obtained, while allowing recirculation and recycling of low-standard geological polymers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451924A_ABST
    Figure CN119451924A_ABST
Patent Text Reader

Abstract

A method for obtaining a friction material for a brake pad, in which a wet paste formed by mixing an alkaline silicate solution with metakaolin is distributed in the form of a layer or tape on a support, and then the wet paste is subjected to a heat treatment to form geopolymer aggregates; wherein the heat treatment comprises drying the wet paste into fully dried or almost fully dried geopolymer aggregates, the fully dried or almost fully dried geopolymer aggregates having a moisture content that is lower than the desired moisture content in the final geopolymer; and wherein a fully dried or nearly fully dried geopolymer is ground into a powder, which is then rewetted to a desired moisture content by adding water or a hydrated salt.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This patent application claims the priority of Italian Patent Application No. 102022000012338 filed on June 10, 2022, the disclosure of which is incorporated herein by reference in its entirety. Technical Field

[0003] The present invention relates to a method for preparing friction material, in particular friction material for manufacturing brake pads. The present invention also relates to the associated friction material and brake pads manufactured using the friction material manufactured by the method.

[0004] The friction material of the present invention is specifically intended for use in the manufacture of non-asbestos friction layers / blocks for friction elements such as brake elements, i.e., vehicle brake pads or brake shoes, and / or friction discs, which have properties similar to or better than the properties of friction materials in the NAO ("non-asbestos organic friction material"), "low steel" and "semi-metallic" categories. Background Art

[0005] Application EP3128201 published in the name of the same applicant, the entire content of which is incorporated herein by reference for the essential parts thereof, discloses a method for obtaining a binder for brake pads consisting at least 90% of geopolymer, as well as associated friction materials and brake pads.

[0006] In EP3128201, the binder is obtained by dry grinding of caustic soda flakes and subsequent dry mixing of soda powder with kaolin. This process, although chemically efficient, involves a series of potential safety risks for the operator that cannot be ignored. In particular, the dry grinding of caustic soda is a high-risk process and may produce very fine and volatile sodium hydroxide powder that is highly corrosive and irritating, which the operator may accidentally inhale when, for example, opening the grinder to unload the product or during cleaning of the machine. In addition, during or after grinding, the soda powder absorbs large and uncontrolled amounts of moisture from the environment. This uncontrolled residual moisture is retained by the soda powder in the subsequent mixture with kaolin and, if the residual moisture is too high, may be released in the form of steam during the hot forming of the brake pad, leading to serious production problems of the layer / block of the finished friction material - the layer / block of the finished friction material tends to peel and crack.

[0007] In order to overcome this problem, EP3841311, still in the name of the same applicant, discloses a similar process, but using metakaolin instead of kaolin and using an aqueous sodium silicate solution with a minimum amount of sodium hydroxide which can be used as a reactant in any case, the entire content of which is also incorporated herein by reference as an essential part of this document.

[0008] According to EP3841311, in addition to metakaolin, other sources of aluminum silicate, such as kaolin or fly ash, can also be used. However, kaolin has a very long reaction time, and one disadvantage of fly ash is that suppliers cannot provide components that do not change over time. Therefore, metakaolin is preferred.

[0009] Still according to EP 3841311, other raw materials may be used under appropriate conditions, for example common sources of silicon dioxide such as quartz, or colloidal silicon dioxide dissolved in alkaline sodium or potassium hydroxide solution.

[0010] In any case, EP3841311 teaches a method in which the wet mortar produced by adding the above-mentioned alkaline silicate solution to the metakaolin by mechanical mixing is subsequently dried by an atmospheric pressure drying process at a temperature ranging from 20°C to 300°C, which can also be adjusted until a vacuum state is reached (i.e. a value equal to or greater than 0.018 mBar). Drying is generally carried out at a temperature ranging from 80°C to 200°C at atmospheric pressure to obtain a dry product in the form of a ribbon having a weight loss ranging from 5% to 40% relative to the initial weight and an associated residual moisture of less than 30% of the final weight. The product is then ground to a size less than or equal to 800 microns, preferably less than 400 microns, and the resulting powder material is used as a binder for the production of mixtures / compositions for brake pads similar to those disclosed in EP3128201.

[0011] Subsequent tests carried out by the applicant's technicians both in the laboratory and by test drives on real vehicles have now shown that the content of residual moisture in the geopolymer powder used as raw binder in the friction composition must be adjusted with great precision, i.e. any value of residual moisture less than 30%w (by weight) is not sufficient, but rather the residual moisture must be kept within a predetermined range, which has proven to be extremely difficult to meet when operating with the method of EP3841311, which may lead to considerable amounts of waste in production, which, moreover, cannot be recycled, with a net economic and energy loss. Summary of the invention

[0012] The object of the present invention is to provide a method for manufacturing a friction layer / block for a friction element such as a brake element, for example a vehicle brake pad or brake shoe, and a method for preparing the related friction material and the corresponding inorganic binder, which do not have the above-mentioned problems of the methods of both EP3128201 and EP3841311, and thus facilitate obtaining a friction material and an associated brake pad that resist the heat generated during braking, while providing satisfactory braking performance, optimal friction characteristics and ease of manufacture.

[0013] Another object of the present invention is to provide a manufacturing method that allows easy recycling and recovery of geopolymers that are accidentally produced and have sub-satisfactory standards.

[0014] The present invention therefore relates to a method of producing a friction layer / block for a friction element, such as a brake element, for example a vehicle brake pad or brake shoe, as defined in the appended claims.

[0015] The invention also relates to an associated binder and a friction material containing such a binder, and to an associated friction element, in particular a brake pad or a brake shoe, which has a friction layer or a block produced by the method according to the invention.

[0016] In particular, the friction material according to the method of the invention comprises as its constituent materials: inorganic and / or organic and / or metallic fibers; a binder consisting almost entirely or completely and exclusively of a geopolymer or a mixture of geopolymers; at least one friction modifier or lubricant, for example comprising sulfur and / or carbon materials or nanomaterials; and at least one inorganic or metallic filler or abrasive, wherein, however, the main grinding action in the friction material of the invention is performed by the geopolymer matrix of the pad produced by the binder.

[0017] Hereinafter, "binder consisting almost entirely of geopolymer" means a binder for friction elements in which the geopolymer or the geopolymer composition or mixture constitutes at least 90% by weight of the total amount of binder present.

[0018] The geopolymer binder is present in the composition of the friction material according to the invention in an amount calculated on the basis of the total volume of the friction mixture / composition, preferably, but not necessarily, equal to or greater than 5% by weight, or even more preferably comprised between 20% and 60% by weight. In fact, experiments have shown that, depending on the type of geopolymer used as binder and on the nature of the other materials used in the composition, in the case of too little amount of inorganic binder, the mechanical properties necessary for its use as a friction material cannot be achieved.

[0019] Therefore, the friction material according to the method of the present invention is almost completely or completely free of organic binders (organic binders may be present in a maximum amount equal to or less than 10% by weight), and for this reason, the friction material according to the method of the present invention does not undergo thermal degradation by oxidation at high temperatures, for example greater than 300° C. and up to more than 600° C.

[0020] The geopolymer binder, which is produced according to the method of the invention and is used in the friction material according to the invention as the sole and main binder in the complete or almost complete absence of conventional organic binders and therefore as the prevalent binder (i.e. constituting at least 90% of the total binder present), is obtained by chemical reaction starting from inorganic precursors, such as SiO2 and Al2O3, and among these, in particular, use is made of commercial sodium (and / or potassium) silicates, for example those from the company “PQ Corporation—Holland”, possibly with the addition of small amounts of sodium or potassium hydroxide (in any case, the sodium silicates also function in the almost complete absence of hydroxides), and commercial metakaolin, for example by reacting the metals of the company “Imerys Refractory Minerals—Argical-M The metakaolin obtained by high temperature calcination of kaolin from the company "1200S", containing about 55% by weight of SiO2 and 39% by weight of Al2O3 as well as impurities of Fe2O3, TiO2, K2O, Na2O, Cao and MgO, is generally assumed to have the following general chemical formula for geopolymer binders:

[0021] Al2O3·2SiO2

[0022] The inorganic geopolymer binder according to the invention can be prepared in premixed form and then incorporated as such to all the other constituent materials of the mixture of the friction material, preferably in a Loedige mixer or in any of the other mixers commonly used for friction materials, such as an Eirich mixer. The unfinished compound thus obtained is then subjected to a molding process to produce the desired friction element, such as a brake pad or brake block.

[0023] However, according to a preferred embodiment of the present invention, the inorganic geopolymer binder is instead prepared during the mixing step of the overall friction composition to directly produce the raw friction compound to be subsequently formed into a friction material block having the desired properties.

[0024] Synthesis of Geopolymer Binders

[0025] Analogously to the method of EP 3841311, the geopolymer binder to be used in the friction composition for brake elements is prepared from metakaolin, which is reacted with an aqueous solution of caustic soda and / or potash, wherein sodium silicate is added to the caustic soda solution, thereby forming an amorphous geopolymer which can, if necessary, be converted into at least partially crystalline form only by further heat treatment.

[0026] The following description will refer only to sodium compounds without loss of generality as it will be apparent to one skilled in the art that the same techniques can also be used with reference to potassium compounds.

[0027] First, sodium silicate in any form is dissolved in water with the possible addition of commercially available soda granules to form an alkaline sodium silicate aqueous solution (e.g. by adding caustic soda). Metakaolin is then added to the alkaline aqueous solution either all at once or gradually while mixing, or vice versa, the alkaline soda and silicate solution is gradually added to the metakaolin powder until a homogeneous paste is obtained with a relatively high SiO2 / Al2O3 ratio, which is maintained in the range / interval between 3 and 10, i.e., taking "x" as the molar ratio of SiO2 / Al2O3, the effective ratio must be:

[0028] 3 <x<10

[0029] This wet paste, similar to a slurry, is taken out of the mixer and subjected to shaping and drying steps at any temperature conditions up to 300° C. under any atmospheric conditions (thus even under vacuum) using an appropriate shaping and drying system, preferably a casting device, such as the casting device shown (only schematically) in the published Italian patent application No. 102020000015202.

[0030] As already disclosed in the published Italian patent application, the mixing of the silicate solution and the metakaolin may comprise a mixing at a speed between about 500 rpm and about 1000 rpm and for a time between about 1 minute and about 20 minutes.

[0031] The mixing of the silicate solution and the metakaolin may be carried out at a temperature between about 20°C and about 40°C.

[0032] Thereafter, the wet paste / mortar / slurry thus obtained and discharged from the mixer is distributed on a support to form a layer of uniform thickness and is subjected to a thermal treatment in which it is dried to obtain a strip made of dry / semi-dry geopolymer material.

[0033] According to IT102020000015202, the dried tape may have a moisture content comprised anywhere between 0%w and 20%w and a thickness between about 0.1 mm and about 2 mm.

[0034] The support may comprise paper, plastic film or steel sheet. For example, the support may comprise Paper or membrane.

[0035] More generally, according to the invention, the support, for example in the form of an endless belt conveyor, can be made of a specific material suitable for neutral or alkaline pastes / mortars that is insensitive to alkaline environments, such as polyester film or other types of materials suitable for neutral / alkaline pastes / mortars. During shaping of the paste (in this case, also suitable for applying mechanical stresses with high shear stresses to the paste) and drying into a belt, a geopolymerization reaction occurs in which the metakaolin dissolves in an alkaline sodium silicate solution. The oligomers formed then coagulate together to form a 3D geopolymer network.

[0036] The drying step is preferably carried out in a controlled temperature oven (single-stage or multi-stage oven), wherein the controlled temperature oven can have a temperature profile that is regulated by means of a control device. The drying step can be carried out in a discontinuous or continuous manner. When carried out in a continuous manner, a tunnel oven / furnace can be used through which the layer of wet paste distributed on the support passes.

[0037] According to a first main characteristic of the invention, and unlike what is taught in IT102020000015202, instead of attempting to dry the wet paste in a controlled manner so as to reach any desired moisture content already at the outlet of the oven, a drying process preferably carried out at a temperature between 100° C. and 250° C. is carried out so as to obtain a completely dry or almost completely dry aggregate residue consisting of an amorphous geopolymer having a moisture content that is zero or very low, i.e. equal to zero or in any case lower than the desired final moisture content.

[0038] Thereafter, according to a second main feature of the invention, in combination with the first feature described above, this completely dry or almost completely dry geopolymer is re-moistened in a suitable mixer to reach the desired moisture content.

[0039] According to another aspect of the invention, this desired moisture content should be comprised within a very narrow and precise range. In particular, the final moisture content of the geopolymer binder of the invention should be comprised between 4%w and 16%w of the total weight of the geopolymer.

[0040] In fact, it has been experimentally demonstrated that only within this specific and restricted humidity range of amorphous geopolymers it is possible to obtain a friction material that can be easily molded into a block having sufficient strength and elasticity and at the same time produces a block / layer substantially free of cracks or defects and having the desired braking properties.

[0041] Thus, according to the invention, since the moisture content allowed for the geopolymer during the mixing phase (i.e. the step of obtaining the complete friction material mixture / composition) is between 4%w and 16%w, the expression "completely dried or almost completely dried aggregate" refers to an aggregate of geopolymer which, upon leaving the drying phase / step, has a moisture content equal to about zero or at any rate below a value comprised in the interval of 4%w to 16%w, depending on the desired final moisture content, in such a way that it is possible to add directly or indirectly a large amount of water to the geopolymer to rewet the geopolymer to the desired moisture content. Here and hereinafter, "large amount" refers to a final amount of added water / moisture of the order of "n" %w (wherein "n" may be, for example, from about 1 to about 16).

[0042] According to the invention, the dry / almost dry aggregates in the shape of ribbons leaving the oven and formed of amorphous geopolymer are ground and turned into powder using any suitable grinding system, preferably a ball mill or a jar mill or a hammer mill, until a particle size of less than 600 microns, preferably less than 400 microns is obtained.

[0043] Thereafter, according to the invention, the powder thus obtained, whatever its moisture content, is remoistened to reach the desired moisture content within the above-mentioned range of 4%w to 16%w.

[0044] According to different embodiments of the invention, the rewetting process can be carried out before the final mixing stage for obtaining the desired friction material, in which the geopolymer powder is mixed together with the other component materials of the friction material to be obtained, or the rewetting process can be carried out during this same final mixing step, i.e. while preparing the raw (not yet formed) friction material by mixing together the various components of the friction material.

[0045] This second embodiment may be preferred.

[0046] According to different embodiments of the invention, the rewetting process can be performed by adding a desired amount of liquid water to the powdered and dried geopolymer, or by adding a calculated amount of a salt having a chemical and / or physical water content, such as a hydrated salt, to the powdered and dried geopolymer.

[0047] According to another aspect of the present invention, suitable salts for rehydrating dry or nearly dry geopolymers may be selected from an exemplary but non-exhaustive group including sodium carbonate and / or potassium carbonate decahydrate (e.g., Na2CO3*10H20), trisodium phosphate and / or tripotassium phosphate dodecahydrate (e.g., Na3PO4*12H20), sodium sulfate and / or potassium sulfate decahydrate (e.g., Na2SO4*10H20), disodium (or potassium) tetraborate dehydrate (e.g., Na2B4O7*10H20), and any combination thereof.

[0048] Disodium tetraborate dehydrate, while chemically effective, is preferably not used for safety reasons as it is a potentially hazardous product.

[0049] In any case, the rewetting stage can be carried out in all ways, however preferably during the final mixing of all the component materials of the friction material mixture / composition, i.e. the dry or almost dry geopolymer is powdered and then used as a component material of the friction material mixture as such, provided that a rewetting component / agent, such as liquid water or a hydrated salt, is also added together (in combination) with the dry or almost dry geopolymer.

[0050] Embodiments in which liquid water as a rewetting agent is used and added only during the final mixing step of the friction material mixture / composition, i.e. when all other component materials of the friction mixture are also present, may be preferred, since the liquid water also at least partially avoids possible accidental dispersion of the component materials, in particular the geopolymer, in the environment before / during the mixing stage.

[0051] After or during rewetting, the rewetted geopolymer is mixed with other usual ingredients of friction compositions, such as fillers, lubricants, abrasives, fibers, etc., to obtain a friction material mixture formed as in EP3128201. During forming, the previously synthesized geopolymer particles consolidate and remain amorphous, due solely to the application of pressure and temperature, to obtain a friction element, typically a brake pad, in which the constituent materials are dispersed in a matrix consisting only of amorphous geopolymer inorganic binder, except possibly a limited amount of less than 10% of organic binder. According to the invention, it has been experimentally demonstrated that, in order for the geopolymer to be properly consolidated at this stage / step of the manufacturing process, only a precise and limited amount of moisture (direct, or indirect, i.e., water present in hydrated salts) will be present in / with the geopolymer, a precise and limited amount of moisture (direct, or indirect, i.e., water present in hydrated salts) comprised between 4%w and 16%w by weight, and preferably comprised between 8% and 12%, both end values ​​of the aforementioned intervals.

[0052] The friction element thus obtained does not produce rejects due to cracks or flaking even when using pressures of the order of tens of MPa. The result is that the powder is reconsolidated under molding conditions comparable to those of EP3841311 and under normal molding conditions of brake pads, resulting in braking performance comparable to that of the friction material produced by hydrothermal synthesis according to EP3841311, and with material and disc wear comparable to that of the same component produced according to EP3128201 or EP3841311.

[0053] Forming for reconsolidation of geopolymer powders

[0054] The shaping of the brake pad obtained by the method of the invention is carried out by placing the raw compound (friction mixture) in a mold which also includes a metal support or backing plate that has been subjected to performance treatment and has or does not have a damping / insulating layer known as a "bottom layer" which, when present, not only makes it possible to form a layer or block of friction material above the bottom layer, but also achieves the adhesion of this layer or block to the metal support during the shaping stage.

[0055] Molding is done at a temperature between 40°C and 250°C and 150Kg / cm 2 Up to 2000Kg / cm 2 The method is to form the raw compound or mixture into a mold and then press it at a temperature of 40°C to 250°C at 150 kg / cm 2 Up to 2000kg / cm 2 This is accomplished by molding the preform compound onto the backing sheet at a pressure of (14.7 MPa-196 MPa) for a period of time ranging from 3 minutes to 15 minutes.

[0056] Alternatively, the raw compound may be molded to obtain the friction material block, which is then simply attached to the metal support or backing plate (with or without a primer layer) using, for example, phenolic or silicone-based glue.

[0057] Other components of friction materials

[0058] The components of the composition or starting compound of the friction material to be produced according to the present invention may be those used in the friction materials known in the art, wherein the only precaution is to completely replace the existing organic binder with the inorganic binder obtained by the method described above, while reducing the content of abrasive and increasing the content of lubricant.

[0059] The friction material obtainable according to the invention is also preferably free of copper and / or copper alloys, both in the form of powder and fibers.

[0060] In particular, the component made of fibers may include any organic or inorganic fiber except asbestos, or any metal fiber commonly used in friction materials, preferably excluding copper and copper alloys. Illustrative examples include inorganic fibers such as glass fibers, wool or rock fibers, wollastonite, sepiolite and attapulgite, and organic fibers such as aramid fibers, polyimide fibers, polyamide fibers, phenolic fibers, cellulose and acrylic fibers or PAN (polyacrylonitrile), metal fibers such as steel fibers, stainless steel, aluminum fibers, zinc, etc.

[0061] The fibers may be used in the form of staple fibers or powder.

[0062] The amount of fibers is preferably between 2 and 30 volume % and more preferably between 8 and 15 volume % of the total volume of the friction material, and the fiber component preferably always comprises rock fibers which have been shown to have a strong affinity with geopolymers used as binders.

[0063] Many materials known in the art can be used as organic or inorganic fillers. Illustrative examples include precipitated calcium carbonate, barium sulfate, magnesium oxide, calcium hydroxide, calcium fluoride, slaked lime, talc, mica.

[0064] These may be used alone, or may be used in combination of two or more. The amount of these fillers is preferably between 2% and 40% by volume, based on the total composition of the friction material.

[0065] In addition to carbon materials or nanomaterials such as graphene, friction modifiers (which may include all or part of the filler) may also include organic fillers such as cashew powder, rubber powder, powdered tread rubber, various unvulcanized rubber particles, various vulcanized rubber particles, inorganic fillers such as barium sulfate, calcium carbonate, calcium hydroxide, vermiculite and / or mica, abrasives such as silicon carbide, aluminum oxide, zirconium silicate, metal sulfide-based lubricants such as molybdenum disulfide, tin sulfide, zinc sulfide, iron and non-ferrous metal sulfides, metal particles other than copper and copper alloys, and / or combinations of the above.

[0066] Abrasives can be classified as follows (the following list is illustrative only, not necessarily exhaustive and not limiting):

[0067] · Mild abrasives (Mohs 1-3): talc, calcium hydroxide, potassium titanate, mica, kaolin, vermiculite;

[0068] Medium abrasives (Mohs 4-6): barium sulfate, magnesium oxide, calcium fluoride, calcium carbonate, wollastonite, calcium silicate, iron oxide, silicon dioxide, chromite, zinc oxide;

[0069] Strong abrasives (Mohs 7-9): silicon carbide, zircon sand (zirconium oxide), zirconium silicate, zirconium, corundum, aluminum oxide, mullite.

[0070] Preferably, but not necessarily, the friction material obtainable according to the invention contains no strong abrasives but only medium or mild abrasives, since the geopolymer produced as a binder is itself already medium abrasive.

[0071] The friction material produced according to the invention may also preferably comprise graphite in an amount between 5% and 15% by volume, based on the total composition of the friction material.

[0072] Depending on the desired friction properties, the total content of lubricant may preferably be between 4% and 20% of the overall volume of the friction material, and may in particular comprise graphene.

[0073] Curing and coating

[0074] When the formulation and / or design specifications require, the molded product (brake pad) which is cured during pressing and is usually already ready for use after this simple press-forming can optionally be further post-cured by a supplementary heat treatment at 80° C. to 450° C. for a period of between 10 minutes and 15 hours, then sprayed or powder coated, oven dried and, if necessary, possibly machined to produce the final product.

[0075] The friction material obtained by the process of the invention, either after simple press-forming or after a possibly optional supplementary heat treatment, can be used in applications such as disc brake pads, brake shoes and linings for cars, trucks, trains and various other types of vehicles and industrial machinery, or in clutch discs. BRIEF DESCRIPTION OF THE DRAWINGS

[0076] The invention will now be described in more detail with reference to non-exhaustive and non-limiting practical examples of ways of implementing the invention and with reference to the figures of the accompanying drawings, in which:

[0077] - Figure 1 Schematically illustrates a sequence of steps of the method of the present invention and a possible embodiment of an apparatus for performing the method of the present invention;

[0078] - Figure 2 a) to e) illustrate pictures of consolidated samples of the same geopolymer composition prepared at different moisture levels, i.e. having different moisture contents;

[0079] - Figures 3 to 5is a graph showing a comparison of mechanical properties of identical friction material mixtures / compositions comprising the same geopolymer composition and obtained using the method of EP3841311 (reference A) and the method of the present invention using different amounts of liquid water and therefore having different degrees of humidity / moisture content, including compressibility ( Figure 3 ),hardness( Figure 4 ) and density ( Figure 5 );

[0080] - Figure 6 The main steps of the production method of brake pads according to two different embodiments of the invention and according to the prior art, namely EP3841311, are illustrated in a comparative manner and via a sequential block diagram, wherein the production method of brake pads according to the prior art is marked as "classic method";

[0081] - Figures 7 to 9 is a graph showing a comparison of mechanical properties of the same friction material mixes / compositions comprising the same geopolymer composition and obtained using the method of EP3841311 (reference B) and the method of the present invention using the same humidity, i.e. having the same moisture content (10%w) obtained by adding different hydrating salts, including compressibility ( Figure 7 ),hardness( Figure 8 ) and density ( Fig. 9 );as well as

[0082] - Figures 10 to 12 A graph showing a selection of the most representative parts of the results of the same AK Master brake test performed on brake pads produced with friction materials according to the prior art of references A and B and with friction materials according to the method of the invention, wherein the friction materials according to the method of the invention were produced to have the same moisture / humidity content, which was reduced by adding liquid water ( Fig.10 ) or by adding different hydrated salts ( Fig.11 and Fig.12 )get, Fig.10 Also included are pictures of the brake pads and associated brake discs used in the AK Master test and the corresponding degrees of wear are shown. DETAILED DESCRIPTION

[0083] The Examples and Comparative Examples are reported herein for illustrative purposes and are not intended to limit the present invention.

[0084] The device according to the invention

[0085] Reference Figure 1 , purely schematically, shows a device or an installation 2 which is configured to carry out the method according to the invention for producing a brake pad 1 and which itself is also part of the invention, and an associated brake pad 1 obtained with the method carried out by the device 2 .

[0086] The device or facility 2 can be continuous or batch type. In the non-limiting embodiment shown, it is continuous and is configured to perform a plurality of different operations / steps in a time sequence in a corresponding number of dedicated devices. In a continuous facility, these dedicated devices are also Figure 1 Arranged in physical order along direction D, the device or facility 2 comprises:

[0087] a first mixer 3 of any known type, preferably a dispersing mixer, into which an alkaline silicate aqueous solution 4 and metakaolin 5 are added and mixed together to obtain a semi-liquid geopolymer paste / slurry 6; such geopolymer paste may be formed using, for example, an alkaline silicate solution, such as a sodium silicate solution, a potassium silicate solution, a lithium silicate solution or any other chemically equivalent aqueous solution. The mixer 3 may be equipped with a temperature control system 30 of any known type;

[0088] a casting machine 7 of any known type configured to cast the newly formed geopolymer 6 in the form of a layer / strip 8 of substantially uniform thickness, the layer / strip of geopolymer being made to rest on a support 9; preferably, the casting machine 7 is equipped with an endless belt conveyor 10, the upper surface of the upper branch of which forms the support 9. The machine 7 is preferably equipped with a blade 11 to uniformly reduce the thickness of the layer / strip of geopolymer 8 to any selected value comprised between 0.2 mm and 2 mm, and with a pressing device (not shown) capable of pressing the geopolymer paste with a predetermined force F;

[0089] a hot air oven or furnace 12 through which the conveyor 10 passes, in the non-limiting embodiment shown relating to a continuous tape-casting machine 7, and which is preferably a tunnel oven / furnace. According to an aspect of the invention, the oven 12 is configured to bring the layer / belt 8 of geopolymer paste / slurry to a completely or almost completely dry state 8b, wherein the expression "completely or almost completely dry state" refers to a state in which the geopolymer aggregate discharged from the furnace / furnace 12 has a moisture content equal to about zero or in any case lower than a value comprised in the interval 4%w to 16%w, depending on the desired final moisture content in the friction material;

[0090] a mill 14 (e.g. a ball mill or a jar mill, preferably a hammer mill), arranged downstream of the oven / furnace 12 (with reference to direction D) and fed, for example, by the conveyor 10, the mill 14 being configured to receive the dry or almost dry geopolymer 8b and comminute it into a powder 8c having a predetermined particle size range of 1 micron to 500 microns, and preferably comprised between 1 micron and 100 microns;

[0091] at least a moisture detector 18 arranged downstream of the oven / furnace 12 and configured to detect the moisture of the reacted geopolymer as it leaves the oven / furnace 12;

[0092] a second mixer 20 of any known type (e.g. a Loedige mixer or an Eirich mixer), arranged downstream of the mill 14 and configured to receive the dry or almost dry geopolymer 8b comminuted into powder 8c and a predetermined amount of water in the form of liquid water or hydrated salts. The mixer 20 is configured to re-moisten the dry or almost dry geopolymer powder 8c to a precise moisture content substantially equal to or lower than the moisture content of the reacted geopolymer 8 at the outlet of the casting machine 7. The mixer 20 may also be configured to receive all the other constituent materials of the friction material to be obtained, which are present in the Figure 1 Indicated by arrow 21. According to a different (and possibly preferred) embodiment - the embodiment in Figure 1 In the diagram, the second mixer 20 (in this case a Loedige mixer or an Eirich mixer) is configured only to re-moisten the powder 8c to a predetermined moisture value by adding liquid water directly or indirectly by adding water by means of the addition of hydrating salts, and the device or installation 2 comprises a third mixer 20b, which is arranged downstream of the mixer 20 and is configured to receive the re-moistened, precisely hydrated geopolymer 8d (dashed arrow) from the mixer 20 and all other component materials 21 of the friction material to be obtained. In both cases, what leaves the mixer 20 (or 20b) is the "unprocessed" or "original" friction material mixture / composition 25;

[0093] Any known type of shaping device 26 - illustrated as a block for simplicity, which receives a "green" or "raw" friction material mixture / composition 25 to shape it into a friction material block or layer 27 having only or almost entirely a well-consolidated geopolymer matrix as a binder. The shaping device 26 can be configured to shape the consolidated friction material block 27 directly onto a support or backing plate 28 to obtain a brake pad 1, or to shape the consolidated friction material block 27 and then apply / attach it to a support 28 to obtain a brake pad 1.

[0094] In this way, contrary to the way disclosed in IT102020000015202, it is not necessary to employ sophisticated moisture sensors and complex control devices to provide geopolymer powder 8c with a desired moisture content. In fact, by knowing the initial moisture and weight of the reacted geopolymer 8 in the oven / furnace 12 and its final weight after drying, it is easy to calculate the water / moisture loss of the reacted geopolymer 8 in the oven / furnace 12, and therefore accurately meter the amount of water (or hydrated salt) to be added to the mixer 20.

[0095] Furthermore, as will be shown in more detail below, tests carried out by the Applicant have also shown that, at the same moisture content of the geopolymer, the consolidation of the geopolymer during the shaping step of the friction material in the device 26 is much better than in the case where, according to IT102020000015202, no rewetting step is carried out in the mixer 20 and the desired moisture content in the geopolymer is obtained by means of precise and strict control of the drying step in the oven 12 - which requires continuous monitoring of the instantaneous moisture content of the geopolymer being processed and which also proves to be in any case not easy to obtain due to the inevitable thermal inertia of the entire drying device and of the mass of the geopolymer being processed.

[0096] Reference Figure 6 , for greater clarity, a comparison is shown between a method according to the prior art of EP3841311 and IT102020000015202 (referenced as "classic method") and two different possible embodiments of the present invention, referenced as "Version A.1" and "Version B", all of which are configured to obtain at the end a brake pad 1 having a geopolymer as sole or main binder.

[0097] like Figure 6 As clearly shown in , after obtaining the geopolymer according to any of the methods disclosed in EP3841311, the classical method of the prior art comprises four main steps: a first step, in which the synthesized geopolymer is dried into a band of a defined moisture range; a second step, in which the band of geopolymer is ground to a determined particle size; a third step, in which a friction material mixture or composition is prepared in any suitable conventional manner using the ground geopolymer as a binder; and a fourth step, in which the friction material mixture is shaped to form a brake pad 1 (or to form a friction material block 27, which will then be bonded to a backing plate 28 to obtain a brake pad 1).

[0098] In a first embodiment of the method of the invention, referenced A.1, after obtaining the geopolymer according to any of the methods disclosed in EP3841311, five main steps are performed instead of four:

[0099] A first step, in which the synthetic geopolymer is dried to a moisture content "x", where x ≥ 0% moisture and in any case below the optimum amount (and therefore below the defined moisture range of the classical method);

[0100] A second step in which the dry or nearly dry geopolymer strip is ground to a determined particle size;

[0101] • A third step, wherein a friction material mixture or composition is prepared in any suitable conventional manner by adding all other component materials of the desired friction material mixture to the dry or nearly dry and ground geopolymer;

[0102] a fourth step, in which a specific amount of liquid water calculated to obtain the desired and precisely defined wetness of the geopolymer is added to the friction material mixture prepared in the third step: in this way, the dry geopolymer and the water act in combination as a binder, these two components being generally added in the same mixer together with the other component materials of the desired friction material mixture;

[0103] A fifth step, in which the friction material mixture is shaped to form the brake pad 1 .

[0104] In a second embodiment of the method of the invention, referenced B, after obtaining the geopolymer according to any of the methods disclosed in EP3841311, four main steps are performed:

[0105] A first step, in which the synthetic geopolymer is dried to a moisture content "x", where x ≥ 0% moisture and in any case below the optimum amount (and therefore below the defined moisture range of the classical method);

[0106] A second step in which the dry or nearly dry geopolymer strip is ground to a determined particle size;

[0107] A third step wherein a friction material mixture or composition is prepared in any suitable conventional manner by adding to the dry or nearly dry and ground geopolymer:

[0108] a) All other component materials of the desired friction material mixture, and in combination

[0109] b) a limited amount of hydrated salt - this sub-step b) corresponds to the fourth step of embodiment A.1

[0110] step;

[0111] · Fourth step, in which the friction material mixture is shaped to form the brake lining 1.

[0112] Another embodiment of the method according to the invention is also possible, which is similar to embodiment A.1 and can be labeled as embodiment A.2 (not shown for simplicity), in which five steps are again carried out: the first step and the second step are the same as the corresponding steps in embodiment A.1; the third step comprises adding a defined amount of liquid water to the dry or almost dry geopolymer powder in a first mixer to obtain a wetted geopolymer powder; the fourth step comprises preparing a friction material mixture or composition using the wetted geopolymer powder as a binder in a different second mixer; and the fifth step comprises shaping the friction material mixture to form the brake lining 1.

[0113] Method according to the invention - Operational example

[0114] A silicate solution with appropriate components (produced by mixing water, hydroxides and solid silicate provided by PQ Corporation) is mixed with commercially available metakaolin at a solution / metakaolin weight ratio between 1 and 10 (including 1 and 10) to have an Si / Al molar ratio in the range of 1 < x < 10; preferably, this range can vary from 2 to 6. Different ratios with higher Al or Si content are also possible; however, experimental results and conclusions drawn from theoretical calculations are that the invention operates with maximum efficiency when the Si / Al ratio is between 2 and 6.

[0115] The alkaline silicate solution and metakaolin are mixed by mechanical stirring to obtain the formation of a homogeneous paste.

[0116] The paste thus obtained is dispersed onto a plastic mat using the "casting" technique and dried at a temperature between 70 °C and 250 °C and at atmospheric pressure - the drying time is in the range between 1' (minute) and 90' (minutes), depending on the power of the oven used - so as to reduce the weight of the mixture to up to 10% to 40% of the original weight and convert the mixture into a pure amorphous geopolymer.

[0117] The dried silicate-metakaolin geopolymer system is removed from the dryer and ground using a ball mill. The final water content of the silicate-metakaolin geopolymer system is calculated by considering the maximum amount of water that the system can lose, and this final water content corresponds to 0% powder moisture.

[0118] The geopolymer powder thus produced is re-moistened in a Loedige or Eirich mixer (or other mixer) by adding an appropriate amount of liquid water to a precise and desired moisture content comprised between 4%w and 16%w, and the binder in the form of a hydrated powder thus produced is added to the friction material mixture or other raw materials required for the composition selected for dry mixing using known mixers, such as a Loedige or Eirich mixer.

[0119] The "green" friction material mixture or composition thus obtained can be thermoformed under pressure to obtain a series of brake pads.

[0120] forming

[0121] The shaping stage is accomplished by placing the raw or "unprocessed" compound, and possibly a metal support with a possible underlying layer, in a mold (known and not shown for simplicity) heated to a temperature between 60° C. and 250° C., subjecting the raw compound to a pressure of 150 Kg / cm 2 With 2000Kg / cm 2 The molding pressure is between 100°C and 250°C for a time period between 1 minute and 15 minutes, or the original compound 11 is pre-molded in a mold, and the pre-molded compound is then molded onto a metal support at a temperature between 100°C and 250°C and a molding pressure between 150Kg / cm2 and 2000Kg / cm2 for a time period between 1 minute and 15 minutes.

[0122] Alternatively, the original compound can be molded without a metal support so as to obtain only a block of friction material, which is then subsequently glued to the metal support in a known manner using a phenol-based or silicone-based glue - whether or not the metal support has a (known) insulator / damper layer or a primer layer, for example by pressing the block of friction material against the metal support with a possible primer layer at a temperature of 180°C for 30 seconds.

[0123] In any case, the molding pressure must always be greater than the water saturation pressure at the molding temperature.

[0124] At the end of the above process, an asbestos-free friction material is thus obtained, which includes as component materials inorganic and / or organic and / or metallic fibers, at least one binder, at least one friction modifier or lubricant and at least one filler or abrasive, wherein at least 90% of the binder consists of fully consolidated silica aluminum geopolymer.

[0125] The constituent materials of the original compound are added to the inorganic binder in appropriate amounts so that the total amount of inorganic geopolymer binder is preferably, but not necessarily, equal to or greater than 20% and not greater than 60% by weight of the total volume of the friction material, and even more preferably equal to about 47% by weight.

[0126] After obtaining the binder, but before the curing stage / step (which usually coincides with the forming stage), no asbestos or derivatives or copper or copper alloys are added to the friction material composition as its component materials; therefore, the friction material obtained according to the present invention is substantially free of or almost free of organic binders, substantially free of copper or copper alloys and / or fibers of copper or copper alloys, and preferably, but not necessarily, substantially free of strong abrasives, wherein, here and hereinafter, the term "substantially free" means that the indicated material can be present at most as an impurity; therefore, the at least one abrasive contained in the friction material according to the present invention is preferably, but not necessarily, a medium or soft abrasive; wherein these terms refer to the following categories:

[0127] · Mild abrasives (with a Mohs hardness of 1-3): for example, talc, calcium hydroxide, potassium titanate, mica, vermiculite, kaolin;

[0128] Medium abrasives (with a Mohs hardness of 4-6): for example, barium sulfate, magnesium oxide, calcium fluoride, calcium carbonate, wollastonite, calcium silicate, iron oxide, silicon dioxide, chromite, zinc oxide;

[0129] Strong abrasives (with a Mohs hardness of 7-9): for example, silicon carbide, zircon sand (zirconium oxide), zirconium silicate, zirconium, corundum, aluminum oxide, mullite.

[0130] The volume ratio between the lubricant and the abrasive contained in the friction material to be formed is preferably selected between 1:1 and 1:4 (for comparison, this ratio is generally 1:8 or more in known friction materials having an organic binder).

[0131] Furthermore, the starting raw materials for obtaining the geopolymer binder are selected such that the inorganic geopolymer binder in the friction material according to the invention has a SiO2 / Al2O3 ratio between 3 and 10 and a SiO2 / Na2O ratio between 3 and 10. Densification of the geopolymer powder is obtained during shaping.

[0132] Example 1 - Comparative production of adhesives

[0133] 115.7 g of metakaolin from the company "Imerys Refractory Minerals" were mixed with 300.0 g of an aqueous solution of 139.4 g of sodium silicate in any form (as already indicated, potassium silicate can also work) - in this case from the company "PQ Corporation-Holland" - and 1.51 g of caustic soda in the form of granules previously prepared, at a speed of 800 rpm for a time varying from 5' to 45' using a drill stirrer and a special mixing beater for medium and high viscosity fluids. The wet paste obtained by mixing the metakaolin with the sodium silicate-caustic soda solution was dispersed on a sheet of polyester film dedicated to wet and alkaline pastes / slurries using the following parameters: the thickness of the dispersed paste was between 0.1 mm and 3 mm.

[0134] Thereafter, a number of samples were prepared by drying the wet dispersed paste at temperatures between 40°C and 250°C, with sheet sizes between A3 and A4, and drying times varying between 10' and 90'. Specifically, a reference sample with a controlled humidity of 12%w and a number of samples completely dried to substantially 0%w humidity were prepared.

[0135] The semi-dried and completely dried sample binders in the form of solid aggregates were then individually separated from the sheets and ground by a ball mill rotating at 275 rpm for 14 hours to granulate the products, thereby obtaining powders having a particle size of about 200 μm.

[0136] The semi-dried samples at 12%w humidity were used as is, while the completely dried samples were re-moistened at different degrees of humidity by adding liquid water. The amount of water added to the dry geopolymer (hereinafter also referred to as "GP") powder was calculated to partially or completely meet the amount of water lost during drying. The GP powder and water were mixed in a mechanical stirrer at 20 Hz inside a PE container for 10 minutes.

[0137] A uniform wet powder was obtained, weighed and pressed according to standard parameters: 150°C–20 MPa–10 minutes.

[0138] 12%w of semi-dried GP powder and fully dried powder were also weighed and pressed with the same standard parameters: 150°C–20MPa–10 minutes. Samples in the shape of disks with adequate mechanical properties to be processed were obtained and the physical properties of the samples were tested. The results are reported in Table 1.

[0139] Table 1

[0140]

[0141]

[0142] In Figure 2 a picture of the sample disk thus obtained is shown: Figure 2 a) in shows disk samples obtained using re-wetted dry GP powder at 12% w and 9% w humidity, which show good mechanical properties and are dense and crack-free; Figure 2 b) in shows disk samples obtained using re-wetted dry GP powder at 6% w humidity, which have poor mechanical properties and show cracks; Figure 2 c) in shows disk samples obtained using re-wetted dry GP powder at 3% w humidity, which apparently have no cracks, but the mechanical properties indicate that consolidation with complete chemical reaction has not occurred. Figure 2 The non-re-wetted sample disk in d) in is a very fragile material and is not evaluable.

[0143] Table 1 and Figure 2 the results in clearly demonstrate the following:

[0144] · The water present in the geopolymers can be regulated by a similar reversible process;

[0145] · Clearly, how a minimum amount of water is needed to ensure good component properties and integrity;

[0146] · A humidity value of 6% may seem good, but the disks are very fragile;

[0147] · Similar results to the re-wetting humidity of 9% wt and 12% wt were obtained using geopolymers with a residual humidity in the range of 0% < x < 6% and adding water to reach a humidity of 9% wt and 12% wt.

[0148] Example 2 - Binder Obtained by Salt Additive

[0149] A hydrated salt additive was used instead of the liquid water additive and the procedure was as in Example 1 for a comparative study of re-wetting the completely dry GP powder (labeled GP25) with a humidity value of 9% in order to compare the resulting mechanical properties using the optimal humidity conditions inferred from Table 1.

[0150] The GP powder was dried overnight at 150 °C to make it completely dry. The measured weight loss was 12% wt. The amount of salt added to each sample of the dry GP25 powder was calculated to match a water content of 9%. A semi-dry 9% w humidity sample (not re-wetted) was used for comparison. The wetted and re-wetted GP25 powders were pressed into sample disks having the same disk shape as in Example 1.

[0151] The salts tested along with their final qualification assessment are listed below in Table 2:

[0152] Table 2

[0153]

[0154] (*) Will not be used for safety reasons

[0155] The mechanical properties of the sample disks are reported in Table 3

[0156] Table 3

[0157]

[0158] As is clearly shown by comparison of Table 1 and Table 3, rewetting by adding salt gave similar or even better results compared to the benchmark (GP25 reference) and to rehydration with water.

[0159] Example 3 - Production of brake pads

[0160] use Figure 1 A plurality of identical brake pads 1 were produced by means of a device or facility 2 schematically shown in the figure, the components of which were selected for laboratory scale. The same friction material formulation was prepared, wherein the average values ​​of the intervals reported in Table 4 below were used for each component, and the powders obtained at different humidity according to Examples 1 and 2 were used as binders, which were indicated as "binder mixtures"; GP powders that were only partially dried after production and grinding and had a humidity of 10% wt were used as benchmark references A and B, and GP powders that were completely or almost completely dried and then rehydrated at different moisture contents by using liquid water or hydrating salts were compared with the benchmark references.

[0161] Table 4

[0162]

[0163] The binder mixture was added to the other ingredients of the mixture according to the following general scheme: binder 20 to 60 wt%, other ingredients 40 to 80 wt%; mixing was done using a Loedige mixer. This system (geopolymer + water) accounted for 47% wt of the friction mixture.

[0164] The friction material mixture / compound thus obtained is then formed into identical brake pads by placing the original or "green" compound and a metal support in a mold. The raw compound is subjected to 250 Kg / cm 2 Up to 720Kg / cm 2The molding pressure lasts for 2 to 15 minutes to allow the molding to proceed step by step.

[0165] The mechanical properties of the friction material block 27 thus obtained were tested. The test results are reported in the form of a bar graph in Figures 3 to 9 middle.

[0166] Similar to studies of pure matrices (eg in EP 3 841 311 ), it was demonstrated how a minimum amount of water is required to activate consolidation.

[0167] The compressibility, hardness and density results confirm that the amount of moisture in the friction material should be above 9% wt in order to have acceptable mechanical properties taking into account the rewetting process.

[0168] It is shown that higher amounts of water are required to achieve consolidation for the test samples obtained by the rewetting method compared to the pure matrix samples.

[0169] The rewetting method of the friction material works in the same way, but gives different (and even better) performances compared to a friction material with the same amount of moisture - where the moisture is already present inside the powder after (partial) drying and is not added in the form of liquid water to the completely or almost completely dry GP.

[0170] About the rewetting method using hydrated salt ( Figures 7 to 9 ), a fixed moisture amount of 10% wt has been chosen to examine which salt works better. A second benchmark B was also chosen to complete the study of AKM characterization.

[0171] This system (geopolymer + water) represents 47% wt of the friction mixture. Rewetting with hydrated salts shows comparable performance to that of the method of rewetting by liquid water, and in some cases even better performance.

[0172] Example 4 - Braking Test

[0173] Brake pads produced as described in Example 3 were subjected to the following tests:

[0174] According to AKM's efficiency test, which includes: settlement braking, braking at different fluid pressures, cold (<50°C) evaluation braking, simulated highway braking, two high-energy braking (first fade test) series interspersed with a regenerative braking series. From this test, it is also possible to infer the wear experienced by the brake pads and brake discs using methods known to those skilled in the art.

[0175] Figures 10 to 12An extract of the results obtained is shown schematically, which represents the most important data of the experimental curves obtained. These diagrams are self-explanatory, also thanks to the descriptive labels inserted in the figures.

[0176] As can be seen, the experimental AKM results for braking performance are very similar and quite comparable (if not better, especially for the rewetting salt method) to those of the benchmark sample obtained according to EP3841311.

[0177] Table 5 below shows the Fig.10 Results of wear comparison tests on materials.

[0178] Table 5

[0179]

[0180] As can also be seen, the wear is similar to the prior art, even though the pads according to the invention are subject to less weight loss due to the better compactness.

[0181] Finally, it can be concluded that the rewetting method to achieve the desired and precise moisture content in the final friction material is a successful one: the control of the production process is considerably better and easier; in case of error, the rehydrated GP can be fully recovered by drying it completely and then rewetting it again. Furthermore, a very precise moisture content control with reproducible results can be obtained, and surprisingly it was found that the moisture content is just within the optimal limited range, thus ensuring a more constant braking performance in different batches of production.

[0182] Therefore, the present invention has the following advantages:

[0183] The moisture content of the powder can be adjusted due to complete or partial drying;

[0184] Adding the desired amount of water in a second step in order to have lower limits for the production of geopolymer powder and in particular to obtain humidity control during the process, allowing to always have an acceptable humidity range;

[0185] · Waste materials ultimately derived from the production of geopolymer powders can be recycled;

[0186] • The use of liquid water during friction material production has a secondary positive effect on reducing the volatile powder of the mixture, thanks to the liquid water holding the fine powder fraction in the mixture.

[0187] Thus, all objects of the invention are achieved.

[0188] Specific terms

[0189] Although certain braking devices, systems, and methods have been disclosed in the context of certain exemplary embodiments, it will be understood by those skilled in the art that the scope of the present disclosure extends beyond the specific disclosed embodiments to other alternative embodiments and / or uses of embodiments and certain modifications and equivalents thereof, such as brake displays for brake drum-based braking systems. Use with any structure is expressly within the scope of the present invention. Various features and aspects of the disclosed embodiments may be combined or substituted with one another to form different modes of assembly. The scope of the present disclosure should not be limited by the specific disclosed embodiments described herein.

[0190] Unless expressly stated otherwise or otherwise understood within the context in which it is used, conditional language such as "can," "can," "might," or "may" is generally intended to convey that certain embodiments include or exclude certain features, elements, and / or steps. Thus, such conditional language is generally not intended to imply that features, elements, and / or steps are in any way essential to one or more embodiments.

[0191] Unless expressly stated otherwise, the terms "approximately," "about," and "substantially" as used herein refer to an amount that is close to the stated amount and still performs the desired function or achieves the desired result. For example, in some embodiments, as the context may indicate, the terms "approximately," "about," and "substantially" may refer to an amount that is within a range of less than or equal to 10% of the stated amount. Likewise, the term "substantially" as used herein refers to a value, amount, or characteristic that primarily includes or tends toward a particular value, amount, or characteristic.

[0192] The present disclosure explicitly contemplates that the various features and aspects of the disclosed embodiments can be combined or substituted with each other. Therefore, the scope of the present disclosure should not be limited by the particular disclosed embodiments described above, but should only be determined by a fair reading of the appended claims and their full equivalent scope.

Claims

1. A method for manufacturing a friction material block or friction material layer which does not contain asbestos and is not sensitive to thermal degradation in use, said method comprising the steps of: preparing a wet paste formed by mixing an alkaline silicate solution with a material selected from the group consisting of metakaolin, kaolin, fly ash and mixtures thereof, preferably only with commercially available powdered metakaolin; and distributing said wet paste on a support to form a layer or strip which is subsequently subjected to a heat treatment to form a geopolymer aggregate; characterized in that: a) - the heat treatment consists in drying the wet paste in an oven / furnace to obtain a completely dry or almost completely dry geopolymer aggregate having in any case a moisture content lower than the desired moisture content to be obtained in the geopolymer; the method further comprises the steps of: b) - grinding the completely dry or almost completely dry geopolymer aggregate into a powder; c) - rewetting the completely dry or almost completely dry geopolymer powder to the desired moisture content; d) - using the ground and remoistened powder as an inorganic binder in a friction material compound, mixing said inorganic binder with inorganic and / or organic and / or metal fibers, with at least one friction modifier or lubricant and with at least one filler or abrasive, in order to obtain an initial friction material compound having exclusively or almost exclusively said ground and remoistened geopolymer aggregates as a binder; e) - Thermoforming the raw friction material compound at between 40° C. and 300° C. to obtain a friction material mass with at least 90% geopolymer as binder.

2. The method according to claim 1, characterized in that Step c) is performed so as to obtain a final moisture content comprised between 4%w and 16%w, calculated on the basis of the total weight of the geopolymer binder after rewetting.

3. The method according to claim 1 or 2, characterized in that: The rewetting step c) is performed by adding a predetermined amount of liquid water to the completely dry or almost completely dry geopolymer powder.

4. The method according to claim 1 or 2, characterized in that: The rewetting step c) is performed by adding a predetermined amount of hydrated salt to the completely dry or almost completely dry geopolymer powder.

5. The method according to claim 4, characterized in that The hydrated salt is selected from the group comprising sodium carbonate or potassium carbonate decahydrate (e.g., CNa2CO3*10H20), trisodium phosphate or tripotassium phosphate dodecahydrate (e.g., Na3PO4*12H2O), sodium sulfate or potassium sulfate decahydrate (e.g., Na2SO4*10H2O), and any combination thereof.

6. The method according to any one of the preceding claims, characterized in that During and together with the mixing step d) a rewetting step c) is performed to obtain said initial friction material compound having exclusively or almost exclusively said ground, rewetted geopolymer aggregate as binder.

7. The method according to any one of the preceding claims 1 to 5, characterized in that Prior to the mixing step d), a rewetting step c) is performed directly on the completely dry or almost completely dry geopolymer powder obtained after step b) using a Loedige mixer or an Eirich mixer, preferably by adding the completely dry or almost completely dry geopolymer powder and a large amount of liquid water into the mixer.

8. A method for obtaining an inorganic binder for an asbestos-free friction material which is not susceptible to thermal degradation during use, said method comprising the steps of preparing a wet paste formed by mixing an alkaline silicate solution with a material selected from the group consisting of metakaolin, kaolin, fly ash and mixtures thereof, preferably only with commercially available powdered metakaolin; and distributing said wet paste on a support to form a layer or strip which is subsequently subjected to a thermal treatment to form a geopolymer aggregate; characterized in that: a) - the heat treatment consists in drying the wet paste in an oven / furnace to obtain a completely dry or almost completely dry geopolymer aggregate having in any case a moisture content lower than the desired moisture content to be obtained in the geopolymer; the method further comprises the steps of: b) - grinding the completely dry or almost completely dry geopolymer aggregate into a powder; c) - rewetting the completely dry or almost completely dry geopolymer powder to the desired moisture content, the ground and rewetted geopolymer aggregates constituting the inorganic binder.

9. An inorganic binder for a friction material which does not contain asbestos and is not susceptible to thermal degradation during use, characterized in that The inorganic binder is obtained by the method according to claim 8.

10. A brake pad (1), comprising an asbestos-free friction material block (27), the asbestos-free friction material block (27) comprising as component materials inorganic fibers and / or organic fibers and / or metal fibers, at least one binder, at least one friction modifier or lubricant and at least one filler or abrasive, characterized in that: The binder is completely or almost completely and exclusively inorganic, consists at least 90% of an amorphous geopolymer or a mixture of amorphous geopolymers and is obtained by the method according to claim 1 .

11. The brake pad (1) according to claim 10, wherein: The volume ratio between the lubricant and the abrasive contained in the friction material of the friction material block (27) is selected between 1:1 and 1:

4.

12. A device or an installation (2) for producing a brake pad (1) having a friction material mass (27), wherein: The binder is completely or almost completely and exclusively inorganic, at least 90% of which consists of an amorphous geopolymer or a mixture of amorphous geopolymers; the device (2) comprises: a first mixer (3), such as a dispersing mixer, configured to receive and mix the alkaline silicate aqueous solution (4) and the metakaolin (5) to obtain a semi-liquid geopolymer paste or slurry (6); a tape casting machine (7) configured to cast the newly formed geopolymer (6) in the form of a layer or strip (8) of substantially uniform thickness and to allow the newly formed geopolymer (6) to rest on a support (9); a hot air furnace or oven (12) configured to receive a layer or strip (8) made of the geopolymer paste or slurry; a mill (14) arranged downstream of the oven or furnace (12), the mill (14) being configured to comminute the layer or strip (8) made of the geopolymer paste or slurry into a powder (8c) having a predetermined particle size range; It is characterized in that a) the hot air furnace or oven (12) is configured to bring the layer or strip (8) made of the geopolymer paste or slurry to a completely or almost completely dry state (8b); b) the mill (14) is configured to receive a dry or nearly dry geopolymer (8b) for comminuting the dry or nearly dry geopolymer (8b) into a dry or nearly dry geopolymer powder (8c) preferably comprising a particle size between 1 micron and 100 microns; The device (2) further comprises: at least a moisture detector (18) arranged downstream of the oven / furnace (12), the moisture detector (18) being configured to detect the moisture of the reacted geopolymer after the oven / furnace (12); a second mixer (20) arranged downstream of the mill (14) and configured to receive the dry or nearly dry geopolymer (8b) pulverized into a powder (8c) and a predetermined amount of water in the form of liquid water or a hydrated salt, the second mixer (20) being configured to re-moisten the dry or nearly dry geopolymer powder (8c) to a precise moisture content equal to or lower than the moisture content of the reacted geopolymer (8) at the outlet of the casting machine (7); The device (2) is constructed as follows: o the second mixer (20) is configured to further receive all component materials of the friction material; or o the second mixer (20) is configured only to re-moisten the powder (8c) to a predetermined moisture value by adding liquid water directly or indirectly by adding water by means of the addition of hydrating salts, the apparatus (2) further comprising a third mixer (20b) arranged downstream of the second mixer (20) and configured to receive the re-moistened precisely hydrated geopolymer (8d) and all other component materials (21) of the friction material; a shaping device (26) configured to receive the friction material composition (25) obtained in the second mixer or the third mixer to shape the friction material composition (25) into a friction material block or a friction material layer (27) having only or almost completely a well-consolidated geopolymer matrix as a binder.

Citation Information

Patent Citations

  • Friction material, in particular for the manufacturing of a brake pad, and associated preparation methods

    EP3128201A2

  • Method for the preparation of friction material, specifically for the manufacture of brake pads and associated brake pads

    EP3841311A1

  • METHODS AND SYSTEMS FOR SYNTHESISING A GEOPOLYMER

    IT102020000015202